Effects of breeds and spices on water holding capacity and consumers’ acceptability of goat meat (chevon) (2016)
Five muscles, semitehdinosus (ST), Biceps femoris (BF), Longissimusdorsi, (LD), Trceps brachii (TB) and Brachialis (BC) were excised from twelve Goats buck carcasses of two breeds, the West African Dwarf and Red Sokoto, 50g of each muscle was cooked with four different spices; ginger (A) garlic (B), alligator pepper (C) and black pepper (D) to determine their effects on water holding capacity and acceptability of the muscles. The muscles together with the spices were cooked for 20 mutes and cooled to room temperature (about 25°C), Ig of each muscle was removed and pressed to determine the water holding capacity, while the rest of the muscles were served to 10 member taste panel to assess the muscles for acceptability based on their flavour on a 9 point hedonic scale. The results (49.80, 48.30) showed that muscles cooked with ginger (A) had higher water holding capacity while those poked with garlic (B) had the least (28.50, 25.30). Muscles from WAD buck goat (BF 49.80) had higher water holding capacity. Muscles cooked with garlic (B) (8.67, 80) were highly preferred by the taste panelists while muscles cooked with alligator pepper (C) (4.32, 4.15) were least accepted. It was evident from the results this study that spices can improve water holding capacity and acceptability of chevon. Ginger (A) favoured high water holding capacity while garlic (B) is recommended for high flavour and acceptability of chevon.